Developing a capacity-building programme to support a mental health service modernisation pilot project in Lviv region of Western Ukraine. (May 2021) - Power, Tracey; Suvalo, Orest
Abstract : This paper reflects on the development of a capacity-building programme to support a mental health service modernisation pilot project based in the Lviv region of Western Ukraine. National programmes that aim to modernise mental health services now have the experience of other countries on which to draw. The challenges faced by such modernisers have much in common. Nevertheless, although there are lessons to be learned from what has worked well elsewhere, we caution that the local context can have a profound effect on the successful implementation of plans based on best practice.